Utilization Of Sugarcane Filter Cake to Reduce The Use of Cement in Brick Making - Andri Fernando Pakpahan; Ainun Rohana; Sulastri Panggabean (Jurnal Rekayasa Pangan dan Pertanian, 2015)
Sugarcane filter cake can be used in brick-making  to reduce the use of cement.The size, compressive strength and absorption was calculated. This research used non-factorial completely random used design with  filter cake level (A) consisted of three types i.e  (A1= 5%, A2= 15%, A3= 25%). The parameters was size, compressive strength and absorption. The result showed that sugarcane filter percentage had significant effect on size, compressive strength and absorption. The highest measure  was  at level 25% and the lowest was at  filter cake of 5%. The highest compressive strength value obtained at 5% level of filter cake and lowest value obtained at 25%  filter cake. The highest absorption filter cake was obtained at  25% and the lowest was  at 5% level.   Keywords: Brick, Filter Cake, Waste.